Konsep Desain Taman Lingkungan Berbasis Partisipasi Masyarakat di Kelurahan Tanah Baru Kecamatan Bogor Utara: indonesia - Dewi, Indarti Komala; Febriani, Yusi; Djakakapermana, Ruchyat Deni; Widyana, Ifanny; Hakim, Mochamad Azizul (Jurnal Lanskap Indonesia, 2024)
Residential in RT 06/RW03 Kelurahan Tanah Baru has a green open space with an area of +1,012 m2. The current condition of the green open space is not well organized and has no design so the site becomes shrubs and some corners of the green open space become. garbage dump. The problem is that there is no clear concept in the arrangement of green open spaces, which can be used as a guide by RT06/RW03 officials and residents in developing green open spaces in the future. The aims of this study were: 1) to identify the needs and desires of residents in designing neighborhood parks; 2) to analyze the site of the neighborhood park 3) to develop neighborhood park design concepts. Analysis using descriptive statistics, site analysis, and the design concept using Permaculture. The community's desire for the function of green open space is as a productive garden, sport, recreation, gathering, and education. The spatial concept consists of welcoming areas, production zones, reuse and service zones, and Social zones. The concept of circulation on the site uses two circulation patterns, namely radial and linear patterns which have achieved effectiveness. The main concept of vegetation management is the production function which includes annual crops, pulses, medicinal plants, and flowering plants that function as edible flowers. The results of the neighborhood park design, make the park sustainable and multifunctional, as: ecological function, Social function, economical functional, and aesthetical function.